Legal Pluralism and Indigenous Rights in Globalized Economies: Examining State Law Interactions with Local Community Justice Systems - Retno Eko Mardani; Geofani Milthree Saragih; Muhammad Khairul Imam (International Forum of Researchers and Lecturers, 2025)
Economic globalization has profoundly reshaped the legal and social structures of indigenous communities, often intensifying conflicts between state law and indigenous law. These conflicts stem from divergent legal norms and the marginalization of indigenous rights within national development agendas. This study investigates the interaction between state law and indigenous law, with particular attention to the impact of globalization and its implications for indigenous rights. Employing a qualitative socio-legal approach, the research utilizes a case study of a specific indigenous community, supported by interviews with indigenous leaders and policymakers, as well as analysis of national and international legal documents. The interpretative method highlights the meaning embedded in legal interactions and the lived experiences of indigenous communities. Findings reveal persistent tensions between state law and indigenous traditions, yet demonstrate that legal pluralism provides a constructive framework for reconciliation. Recognition of indigenous law contributes to social justice and underscores the need for inclusive development policies that promote economic fairness. The study concludes that national legal reforms are essential to strengthen the integration of indigenous law into formal structures, thereby advancing a more equitable and culturally responsive legal system.